Assessing the effect of computerized banking system on the financial operations of South Birim Rural Bank Ltd. - Koranteng, Onassis Addo (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Degree Of Master Of Business Administration (Finance).